The Manuscripts of The Ladder by John Klimakos in the Collection of the Wroblewski Library of the Lithuanian Academy of Sciences - Попова, Татьяна Георгиевна Георгиевна (Slavistica Vilnensis, 2017)
The Wróblewski Library of the Academy of Sciences of Lithuania contains 4 manuscripts of The Ladder by John Klimakos (F19-246, F19-247, F19-248, F19-263). The manuscripts F19-246 and F19-247 reveal great textual proximity. They are associated with the editing of the most popular translation of The Ladder in the Bulgarian environment. Related are the manuscript from the Hilandar Monastery (No. 185) and the manuscript from the Kiev Pechersk Lavra, from the collection of the Library of the Academy of Sciences of Ukraine (No. 235). F19-263 is associated with the editing of the same translation in the Serbian environment. Related is the manuscript from the Pochayiv Lavra, from the collection of the Library of the Academy of Sciences of Ukraine (No. 12). F19-248 contains the text of The Siberian Lestvichnik. The author calls the manuscripts of The Siberian Lestvichnik and the books in the Library of the Lithuanian Academy of Sciences to be containing certain fragments of The Ladder.